2011
DOI: 10.1016/j.cell.2011.07.049
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide Translocation Sequencing Reveals Mechanisms of Chromosome Breaks and Rearrangements in B Cells

Abstract: SUMMARY While chromosomal translocations are common pathogenetic events in cancer, mechanisms that promote them are poorly understood. To elucidate translocation mechanisms in mammalian cells, we developed high throughput, genome-wide translocation sequencing (HTGTS). We employed HTGTS to identify tens of thousands of independent translocation junctions involving fixed I-SceI meganuclease-generated DNA double strand breaks (DSBs) within the c-myc oncogene or IgH locus of B lymphocytes induced for Activation In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
361
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(382 citation statements)
references
References 52 publications
18
361
1
2
Order By: Relevance
“…c. HTGTS 105 . This method combines LAM-PCR and genomewide translocation sequencing 139 to capture genomic rearrangements caused by improper ligation of DSBs between the nuclease target and a spatially proximal off-target site. The target site is used as the 'bait' to capture off-target 'prey' sites, although highly active off-target sites can also be used as the bait, affording a similar distribution of genomic DSBs.…”
Section: Methods To Enhance Cas9-sgrna Precisionmentioning
confidence: 99%
“…c. HTGTS 105 . This method combines LAM-PCR and genomewide translocation sequencing 139 to capture genomic rearrangements caused by improper ligation of DSBs between the nuclease target and a spatially proximal off-target site. The target site is used as the 'bait' to capture off-target 'prey' sites, although highly active off-target sites can also be used as the bait, affording a similar distribution of genomic DSBs.…”
Section: Methods To Enhance Cas9-sgrna Precisionmentioning
confidence: 99%
“…Recently developed techniques for genome-wide translocation sequencing or analysis of chromatin spatial conformation indicate that both the frequency of DSBs at off-target locations by AID (or RAG in immature B-cells) and the spatial proximity between broken chromosomal regions contribute to the high frequency of IgH/c-myc translocations in B-cells during the CSR (or the V(D)J recombination) [265][266][267][268]. What are the respective roles of A-EJ and C-NHEJ in catalyzing IgH/c-myc translocations?…”
Section: End-joining Processes In Chromosomal Rearrangementsmentioning
confidence: 99%
“…In the absence of AID, translocations between these two genetic loci occur at vanishingly low frequency 89 , demonstrating the importance of double-strand breaks as a substrate for translocation. Experimental systems using site-specific, inducible DNA double-strand breaks have also shown that translocation between two sites is highly dependent on the frequency of double-strand breaks 6, 7 . Further evidence for a double-strand intermediate leading to translocation came from an analysis of translocation frequency in p53-knockout mice.…”
Section: Factors Favouring Translocationsmentioning
confidence: 99%